IMPLICAŢII ALE VIZIUNII MODERNE ŞI POSTMODERNE ÎN CURRICULUMUL INTERNAŢIONAL - USM ADMIN (Moldova State University, 2011)
The work presents a theoretical analysis of curriculum field from international perspective. The objective consists in revealing the characteristics of the curriculum paradigms in the modern and postmodern area. Analyses and transposition of the paradigm construct, used in the philosophy of science; establishing an operational definition of the paradigm in the field of the curriculum; analyzing the development of modern and postmodern curri- cular paradigms; identification of the existence of a dominant paradigm or curricular theory in the field of education in Romania.